Legally blonde - Platt, Marc; Kidney, Ric; Luketic, Robert; Metro-Goldwyn-Mayer; MGM Home Entertainment Inc ([United States] : MGM Home Entertainment, 2001)
She's a Beverly Hills beauty who'll do anything to keep her man. Even if it means going all the way...to law school! Elle Woods is a California blonde with couture clothes, fabulous friends and the hottest boyfriend on campus. So when Warner Huntington III suddenly dumps her and heads for Harvard Law School, Elle takes matters into her own perfectly manicured hands. She enrolls too! Now getting Warner back should be a snap, right? Wrong! Elle's about to begin the toughest fight of her life for love, honor, justice and respect for blondes everywhere!
Originally produced as a motion picture in 2001
Director of photograpy, Anthony B. Richmond ; editors, Anita Brandt Burgoyne, Garth Craven ; music, Rolfe Kent ; costume designer, Sophie de Rakoff Carbonell ; production designer, Melissa Stewart
Cast : Reese Witherspoon, Luke Wilson, Selma Blair, Matthew Davis, Victor Garber, Jennifer Coolidge, Holland Taylor, Ali Larter
Keywords: Harvard University. -- School of Law -- Drama; Law students -- Drama; Feature films